CAREGIVER EXPERIENCES, REHABILITATION ACCESS, AND LEGAL PROVISIONS FOR CEREBRAL PALSY IN GUJARAT: A PRAGMATIC REVIEW FOR POLICY INSIGHTS - Bachkaniwala AA, Ramanandi VH, Kakkad AD (Journal of Daoist Studies, 2026)
Background: Families of children with cerebral palsy frequently encounter long-term physical, psychological, social, and financial challenges. In India, the Rights of Persons with Disabilities Act, 2016, provides a rights-based framework encompassing healthcare, rehabilitation, inclusive education, accessibility, and transportation. It is essential to examine the degree to which these provisions correspond with the experiences of caregivers in Gujarat. Objective: To synthesise verified empirical evidence on caregiver burden and rehabilitation access in Gujarat and to interpret the findings against relevant disability-rights provisions. Methods: A focused pragmatic review was conducted utilising Indian empirical studies and legal sources cited within the source manuscript. Bibliographic records and reported findings were meticulously cross-verified against original journal pages, indexed databases, official legislation, or court records. Evidence was systematically categorised into four domains: caregiver strain, social and economic consequences, access to rehabilitation, and rights implementation. Studies not specifically pertaining to cerebral palsy were employed solely for contextual interpretation, and incomplete or unverifiable citations were excluded. Results: Studies conducted in Gujarat consistently demonstrate that the caregiving burden increases in correlation with the child’s dependence and restricted self-mobility. Parents report disruptions in social relationships, health issues, financial difficulties, concerns about the child’s future, inadequate support services, and limited access to trained professionals. Broader evidence from India highlights challenges such as inaccessible transportation, non-inclusive public spaces, stigma, and insufficient welfare support as interconnected sources of burden. These findings are pertinent to statutory responsibilities related to inclusive education, healthcare and rehabilitation, and transportation access. Additionally, a validated Gujarati caregiver burden instrument is available to facilitate the routine identification of families in need of additional assistance. Conclusion: The evidence supports a family-centred interpretation of rehabilitation policy. Service models should combine child-focused therapy with caregiver screening, counselling pathways, decentralised rehabilitation, accessible transport coordination, and practical rights navigation. Current evidence is informative but limited by small, facility-based, and heterogeneous samples; stronger community-based implementation research is required.